A Case Study of Biology Teaching Models in Rattaphumwittaya School Thailand - Maulana, M. Zuhrufi; Peniati, Endah; Widiyaningrum, Priyantini (Journal of Biology Education, 2017)
Science and technology has been included in all aspects of life not as well as education. Rapid changes of science and technology encourages the development and the use of effective teaching model. Thailand, one of the big countries in Southeast Asia, has developed a new curriculum and education system in 2008. This new curriculum and educational system impact on teaching models used. The purpose of this study was to describe the Biology teaching model applied in Rattaphumwittaya School Thailand. This study was a case study by qualitative research. Data were collected by observation, interviews, and documentation. Data were organized in five elements of the teaching model includes syntax, the social system, the principle of reaction, support systems, and the effect of teaching. It was found that the teaching models used includes direct instruction, group investigation, and inquiry training. The selected models for each level Mattayom depend on the student's character. Also, the higher grade , the less teacher dominance during learning.